COMPARATIVE STUDY ON FATIGUE PROPERTIES OF WHEEL MATERIALS CONTAINING INCLUSIONS AND SHRINKAGE DEFECTS (MT) - WANG ZhaoHan; XU Tian; ZENG DongFang; LU LianTao (Jixie qiangdu)
The location of the defect in the CL65 wheel rims was determined by ultrasonic detection, and workblank samples containing the defect were taken out and processed into fatigue samples. Through the fatigue test carried out on Shimadzu electro-hydraulic servo fatigue testing machine, the fatigue life of samples with defects was obtained.After the test, the shape, size and chemical composition of defects were analyzed. The results show that the main component of shrinkage defects is MnS and the main component of inclusion defects is hard oxides. The fatigue life of samples with shrinkage defects is longer than that of samples with inclusion defects. To analyze the difference between the influence of the two defects on the fatigue properties of wheel materials, the finite element models were established based on the tessellated stress theory. Compared with inclusion defects, the tessellated stress at the interface between shrinkage defects and the matrix is significantly reduced and the extent of stress concentration around defects is small. Therefore, the damage of shrinkage defects containing MnS on the fatigue properties of wheel materials is significantly less than that of oxide inclusions.